Formation advertising strategies of Ukrainian pharmaceutical companies with the use of imitative model-simulators - Frolova, Larysa; Semerun, Lyudmyla; Sokolovska, Zoia; Kapustyan, Irene (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
The purpose of the article is to study the various processes in the development of advertising strategies of pharmaceutical companies, based on using tools in a multilevel simulation platform – AnyLogic. From this, the specifics of advertising companies in the pharmaceutical market are determined. The study takes into account the influence of various factors of the market environment on the functioning of pharmaceutical firms, their acceptance of specific advertising strategies, and forecasting the results of their implementation in uncertain conditions. The proposed imitative model-simulator is used to prepare advertising strategies for enterprises in the pharmaceutical industry. The performance of the model is displayed through the results of situational simulation experiments, using the leading Ukrainian Pharmaceutical Company OJSC "Farmak" as an example. The processes of carrying out experiments of different types and the possibilities of parametric adjustment to the experiments are demonstrated. The model is proposed to be used in the process of making strategic decisions and during operational monitoring of pharmaceutical products by an advertising company. Thanks to the modularity and sufficiency of the model, it is possible to customize it to specific industry enterprises.